The Role of Pondok Pesantren Bahrul Ulum Tambakberas on Religious Ethos Surrounding Community - Muhammad Izzul Islam An Najmi; Tutik Hamidah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2025)
Pesantren is a traditional educational environment where students live together and study under the guidance of a teacher who is better known as a kiai. This paper aims to add a special study related to impact of existence in Bahrul Ulum Islamic Boarding School Tambakberas, Jombang, on the Behavior or Attitude the Religious Ethic of Surrounding Community. This paper uses a qualitative research type. And is the result of field research, And is the result of field research, the use of Sociological and Anthropological approaches by understanding socio-religious practices, this writing uses the Theory of Use of Religious Theory as a Cultural System from Clifford Geertz, to see the culture of community around in pesantren. The Bahrul Ulum Tambakberas Jombang as one of subcultural institutions introduced the idea of village Development and a center for community learning activities with Islamic principles that deal directly with all kinds of community problems. The results of writing show that pesantren play a very effective role in empowering and transforming society. Islamic boarding schools were born to respond to the situation and social conditions of a society which is being faced with the collapse of moral foundations, through the transformation of the values offered.